Understanding SCA (Service Component Architecture) - Marino, Jim (Addison-Wesley Professional, 2009)
Use SCA to Simplify the Development and Delivery of Service-Based Applications Service Component Architecture (SCA) is a new programming model that enables developers to build distributed applications more efficiently and effectively than previous technologies. In Understanding SCA (Service Component Architecture), two leading experts offer the first complete and independent guide to SCA. Drawing on extensive experience both developing the SCA standards and implementing large-scale SCA applications, Jim Marino and Michael Rowley provide an insider's perspective for developers and technical managers tasked with architecting and implementing enterprise systems. Rather than simply providing a technology overview, the authors draw on their practical experiences with SCA, explaining The full history behind SCA How SCA fits with other enterprise technologies such as JEE, .NET, Web Services, and BPEL All the major SCA concepts including composition, policy, wires, and bindings Best practices for designing SCA applications Using SCA with Web Services, Message-Oriented Middleware, BPEL, JPA, and Servlets Understanding SCA (Service Component Architecture) provides the background necessary to make informed decisions about when and how to best use SCA to build enterprise applications.